2012
DOI: 10.1097/sla.0b013e31824b32bf
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Controlled, Blinded Trial of Tisseel/Tissucol for Mesh Fixation in Patients Undergoing Lichtenstein Technique for Primary Inguinal Hernia Repair

Abstract: Fibrin sealant for mesh fixation in Lichtenstein repair of small-medium sized inguinal hernias is well tolerated and reduces the rate of pain/numbness/groin discomfort by 45% relative to sutures without increasing hernia recurrence (NCT00306839).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 26 publications
4
104
0
3
Order By: Relevance
“…The discussion on identification of the ''genitofemoral nerve'' (which we entirely agree should be named ''genital branch'') is to some extent semantic as we agree that routine direct identification should not be done, but only if necessary for the herniotomy per se. This may explain our low identification rate of the genital branch (21.3 %) which, interestingly, is within the same range as reported from a recent hernia specialist publication on persistent pain problems, with an identification rate of 26.5 % [3]. Also, we agree that the use of heavy-weight mesh may have contributed to the pain problems, but when the study was conducted there was little conclusive evidence for differences between mesh type and persistent pain.…”
supporting
confidence: 70%
“…The discussion on identification of the ''genitofemoral nerve'' (which we entirely agree should be named ''genital branch'') is to some extent semantic as we agree that routine direct identification should not be done, but only if necessary for the herniotomy per se. This may explain our low identification rate of the genital branch (21.3 %) which, interestingly, is within the same range as reported from a recent hernia specialist publication on persistent pain problems, with an identification rate of 26.5 % [3]. Also, we agree that the use of heavy-weight mesh may have contributed to the pain problems, but when the study was conducted there was little conclusive evidence for differences between mesh type and persistent pain.…”
supporting
confidence: 70%
“…A prospective randomised multicentre trial reports a significant reduction in postoperative pain at 1 and 6 months and a 45 % reduction in incidence of a composite endpoint regarding chronic disabling complications (pain/numbness/groin discomfort) at 1 year after Lichtenstein repair with fibrin glue (heavyweight) mesh fixation compared to standard suture fixation [30]. Two other RCTs comparing, respectively, cyanoacrylate glue fixation (under local anaesthesia) [31] and fibrin glue (under spinal anaesthesia) [32] with standard fixation of a large pore mesh during Lichtenstein repair showed less acute pain at 24 h and lower incidence of hematoma formation and less pain and numbness at 1 week and 1 month.…”
Section: Open Surgerymentioning
confidence: 99%
“…Six studies reported the incidence of chronic pain after inguinal hernia repair [1,8,9,12,13,14]. Five of them reported a lower percentage of chronic pain in the fibrin group, while only one study [14] reported a higher percentage of chronic pain.…”
Section: Resultsmentioning
confidence: 98%
“…However, only five trials reported the recurrence. The recurrence rate in these trails was 1.79% [11], 0.95% [9], 1.35% [8], 0.38% [14] and 0.98% [15], respectively, with the follow-up of 6 to 15 months. One trial [8] determined the recurrence by clinical examination, while others didn't provide specific methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation